Role of Digitalization in the Development of Rural Entrepreneurship in the Gokwe District of Zimbabwe - Robertson K. Tengeh; Patience Z. Moyo; Gabriel O. Ogunlela (An Overview on Business, Management and Economics Research Vol. 3, 2023)
Adopting and implementing digital technologies can assist rural entrepreneurs in accessing national and international markets to increase their profitability. Entrepreneurs in the rural areas of Zimbabwe can leverage digital technologies and infrastructures to develop their businesses within the agricultural sector. Many studies have investigated rural entrepreneurs’ adoption of digital technologies and their impact on their performance. However, little empirical evidence is available on the role of digital technology and how this can assist entrepreneurs in the Gokwe district of Zimbabwe to sustain their businesses. We adopted qualitative and quantitative methodologies to collect data using interviews and questionnaires from rural entrepreneurs. This chapter investigates digital technology’s role in developing rural entrepreneurship in Gokwe. Findings indicate that rural entrepreneurs appreciate the role of digital technology in facilitating networking activities, connecting users, and interacting with suppliers, distributors, customers, and markets to foster their performance and profitability. However, most of them confirmed that they had difficulty identifying new entrepreneurial opportunities and expanding their existing markets with digital technology. Policy implications from this study are the need for government to encourage the adoption of digital technologies to enhance rural entrepreneurs’ businesses.